Comparative Study of the Rhizosphere and Root Endosphere Microbiomes of Cholistan Desert Plants - Mukhtar, Salma; Mehnaz, Samina; Malik, Kauser Abdulla (Frontiers in Microbiology, 2021)
Microbial communities associated with the rhizosphere and roots of desert halophytes play an important role in plants’ growth and development. Very limited information has been available on the microbial diversity of arid environments of Pakistan. Hence in the current study, the microbial diversity of rhizosphere and root endosphere of desert halophytes, Zygophyllum simplex, Haloxylon salicoricum, Aerva javanica, and Capparis decidua was evaluated. The rhizosphere and root endosphere samples of desert halophytes collected from the three geographic sites of Cholistan desert, Punjab, Pakistan were analyzed by using 16S rRNA based Illumina sequencing. The results showed that Proteobacteria were more abundant in the rhizospheric soils while Actinobacteria were more dominant in the root endosphere of halophytes. Bacteroidetes, Firmicutes, and Deinococcus-Thermus were identified from all rhizospheric soils and roots across the three sites, with variable percentage. Bacillus, Kocuria, Pseudomonas, Halomonas, and Flavobacterium were commonly identified from the rhizosphere and root endosphere of halophytes across all the three sites. At the genus level, microbial diversity from Haloxylon showed the greatest variations between the rhizosphere and root endosphere from the site 2. This study revealed that microbial diversity analysis can be used to study how changes in abiotic factors such as soil moisture content and salinity affect the microbial communities associated with the rhizospheric soils and root endosphere of halophytes across the three sites. This study will also help in the discovery of potential inoculants for crops growing in arid and semi-arid regions of Pakistan.